Ownership, economic entrenchment and allocation of capital - Johan E. Eklund; Sameeksha Desai (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
In an efficient economy, capital should be quickly (re)allocated from declining firms and sectors to more profitable investment opportunities. This process is affected by the concentration of corporate control, which in turn is affected by market institutions. We employ a panel of 12,000 firms across 44 countries to estimate the functional efficiency of capital markets. We adapt a measure for the efficiency of capital allocation using the accelerator principle. Our empirical results show weak property rights and highly concentrated ownership reduce the functional efficiency of capital markets. Findings support the economic entrenchment hypothesis but not the legal origins hypothesis.
Keywords: G32; L20; P00; 330; Allocation of capital; accelerator principle; ownership; functional efficiency; economic entrenchment; Finanzmarkt; Allokationseffizienz; Eigentümerstruktur; Wirtschaftskonzentration; Welt